Music and video private copying : an international survey of the problem and the law - Davies, Gillian (Sweet & Maxwell LondonGB, 1993)
Compares the legislation on private copying, in widely differing jurisdictions worldwide. Outlines the solutions being found at national and intergovernmental levels.